2019
DOI: 10.1101/551697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory lesioning induces microglial synapse elimination via ADAM10 and fractalkine signaling

Abstract: Microglia rapidly respond to changes in neural activity and inflammation to regulate synaptic connectivity. The extracellular signals, particularly neuron-derived molecules, that drive these microglial functions at synapses remains a key open question. Here, whisker lesioning, known to dampen cortical activity, induces microglia-mediated synapse elimination. We show that this synapse elimination is dependent on the microglial fractalkine receptor, CX3CR1, but not complement receptor 3, signaling. Further, mice… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…2c). Fractalkine and its receptor, CX 3 CR1, have been recently shown to be required for post-trauma cortical brain neuron microgliamediated remodeling in a mouse whisker lesioning paradigm 21 . We observed that the change of the CX 3 C motif into CX 4 C or AX 3 C blocked the Orion function necessary for the MB pruning ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2c). Fractalkine and its receptor, CX 3 CR1, have been recently shown to be required for post-trauma cortical brain neuron microgliamediated remodeling in a mouse whisker lesioning paradigm 21 . We observed that the change of the CX 3 C motif into CX 4 C or AX 3 C blocked the Orion function necessary for the MB pruning ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, later studies in the cortex using sensory lesion models have given conflicting results. A study using the whisker-trimming model in CR3-deficient mice found that CR3 is dispensable for lesion-induced loss of thalamocortical inputs to the SS cortex in P4-P10 mice, whereas CX3CL1-CX3CR1 signaling is required 48 . Another study examining ocular dominance plasticity (ODP) in V1 cortex of C1q knockout mice showed that basal development of spines on L2/3 neurons were unchanged from P10-P30, and C1q is dispensable for ODP 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Why specific neuronal structures are targeted, given that these complement factors represent secreted soluble proteins, remains unclear. Complement‐independent microglial synaptic elimination has also been demonstrated in other regions, including the hippocampus (Paolicelli et al , ; Weinhard et al , ) and barrel cortex (Gunner et al , ). Finally, in the dLGN, astrocytes also contribute to developmental pruning through TAM receptor‐specific mechanisms (Chung et al , ).…”
Section: Introductionmentioning
confidence: 96%